Praktik Fraud Dalam Kasus Kepailitan Perusahaan - Tanti Wulandari; Andrianto; Ma’ruf Syaban (Majalah Ekonomi, 2021)
This research aims to knowing Fraud Practices that occur in the Bankruptcy process in a company such as well as fraud in the implementation of the process of recording financial statements, effectiveness Internal control, strengthening the code of ethics and triggering the attitude of the Company's leaders. This research approach uses descriptive qualitative research methods and uses Inductive data analysis. Through triangulation techniques, researchers conduct data mining regarding fraud that occurred before the company was declared bankrupt by using data collection techniques with interviews with companies and curators who help deal with this case and then observe the object of research on the data related to fraud. The results of the study show that the practice of fraud often occurs in companies experiencing bankruptcy, in this case in several Processes settlement of bankruptcy, the company has the potential for fraud to occur in it, including Fraud in the Company's financial process, one of which is the Board of Directors combining finance personally with the Company's finances, in addition at the time of the bankruptcy determination tracing only based on the facts of assets alone does not consider the existence of financial statements owned by the company in previous periods. Conditions for Fraud This causes the company to go bankrupt.